Benthic Amphipoda (Crustacea: Peracarida) of the Great Barrier Reef - Lowry, J. K.; Myers, A. A. (Zootaxa, 2009)
Prior to this study there were less than 50 species of benthic amphipods known from the Great Barrier Reef (Haswell 18xx; K.H. Barnard 1931; Berents 1983; Myers 1986; Lowry & Stoddart 1990, 1992; Thomas & Barnard 1991; Lowry & Berents 2005; Guerra-Garcia 2006; Peart 2007a, b; Lowry & Azman, 2007; Yerman & Krapp-Schickel, 2008). Examination of the benthic amphipod fauna of the Great Barrier Reef, based on new collections mainly from the Lizard Island Amphipod Workshop in February/March 2005, revealed 45 families, 116 genera, of which 8 (6.9%) are new, and 256 species, of which 107 (45%) are new. The amphipod fauna of the Great Barrier Reef is the richest fauna yet known from any tropical reef area.